Levels and drivers of urban black carbon and health risk assessment during pre- and COVID19 lockdown in Augsburg, Germany. (1st January 2023) - Liu, Xiansheng; Hadiatullah, Hadiatullah; Schnelle-Kreis, Jürgen; Xu, Yanning; Yue, Mingqi; Zhang, Xun; Querol, Xavier; Cao, Xin; Bendl, Jan; Cyrys, Josef; Jakobi, Gert; Philipp, Andreas; et al.
Abstract: This study aimed to evaluate the levels and phenomenology of equivalent black carbon (eBC) at the city center of Augsburg, Germany (01/2018 to 12/2020). Furthermore, the potential health risk of eBC based on equivalent numbers of passively smoked cigarettes (PSC) was also evaluated, with special emphasis on the impact caused by the COVID19 lockdown restriction measures. As it could be expected, peak concentrations of eBC were commonly recorded in morning (06:00–8:00 LT) and night (19:00–22:00 LT) in all seasons, coinciding with traffic rush hours and atmospheric stagnation. The variability of eBC was highly influenced by diurnal variations in traffic and meteorology (air temperature (T), mixing-layer height (MLH), wind speed (WS)) across days and seasons. Furthermore, a marked "weekend effect" was evidenced, with an average eBC decrease of ∼35% due to lower traffic flow. During the COVID19 lockdown period, an average ∼60% reduction of the traffic flow resulted in ∼30% eBC decrease, as the health risks of eBC exposure was markedly reduced during this period. The implementation of a multilinear regression analysis allowed to explain for 53% of the variability in measured eBC, indicating that the several factors ( e.g ., traffic and meteorology) may contribute simultaneously to this proportion. Overall, this study will provide valuable input to the policy makers to mitigate eBC pollutant and its adverse effect on environment and human health. Graphical abstract: Image 1 Highlights: Regression analysis model allowed to explain for 53% of eBC levels. T, WS, MLH, and traffic density are main drivers for eBC levels. An average about 60% reduction of the traffic flow resulted in ca. 30% eBC decrease. Health risk due to ambient eBC was reduced by about 34% during the lockdown period.